Sintering of MAX-phase materials by spark plasma and other methods; Journal of Materials Science; Vol. 56, iss. 3 - Lyu Jinzhe; Kashkarov E. B. Egor Borisovich; Travitsky (Travitzky) N. Nakhum; Syrtanov M. S. Maksim Sergeevich; Lider A. M. Andrey Markovich (2021, 2021)
Title screen